(untitled) (Journal of the College of Basic Education, 2024)
The prevailing global system characterized as one of American sovereignty, dominance, and power. the United States possessed economic, military, and strategic superiority over all other nations during the Cold War. In order to maintain its hegemonic position and international influence, the United States has adopted a set of strategies and procedures, including dual containment, the war on terror, and adopting the "creative chaos" strategy. Chaos serves as a catalyst for change in Western and American environments, contributing to achieve a strategic objective and shaping a significant geopolitical landscape. However, the repercussions on the affected populations and countries can be detrimental, leading to the perpetuation of instability, conflict, and vulnerability. The concept of "creative chaos" has been prominent in political discourse over the past two decades, retaining a great ambiguity, interpretation, and verbal manipulation. This ambiguity is rooted in the historical events in which the United States orchestrated military disruptions in various countries, then shaped facts that suit its core objectives. In its pursuit of creative chaos, the United States seeks to enhance its own advantages by imposing control over the remarkable systems that govern geopolitical elements .